Characteristics dipole antenna for partial discharge in gas insulated switchgear - Rian Nurdiansyah; Farradita Nugraha; Nadya Glaudira; Linda Faridah (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
The insulation condition of high-voltage equipment can be determined by measuring partial discharge (PD), which is an important indicator in insulation degradation. One of the PD detection methods that can be used is to use antennas as sensors in detecting electromagnetic waves generated from PD activities, especially in gas insulated switchgear (GIS) systems. This study focuses on designing and testing dipole antennas in the ultra-high frequency (UHF) frequency range of 300 Mhz-3 GHz to detect PD signals in GIS. Previous studies on dipole antennas with dimensions of 66×15 mm have reported a bandwidth of 336 MHz and a return loss of -22.4 dB at 1.3 GHz. The antenna was fabricated using an FR4-epoxy substrate with a thickness of 1.6 mm, a substrate radius of 102 mm, and a gap distance of 2 mm. Optimization of the antenna length and width significantly improved performance characteristics. Simulation results show that a dipole antenna with dimensions of 35×40 mm antenna produced a wider bandwidth of 989 MHz with a return loss of −28.47 dB at 1.4 GHz. Experimental validation using vector network analyzer (VNA) and PD testing on GIS confirmed that the optimized dipole antenna effectively detected PD activity at a voltage level of 16 kV.